I.YUSUPOV SHÍǴARMALARÍNDA JÁMIYETLIK-SIYASIY LEKSIKAǴA QATNASLÍ ARABIZMLER - Shaniyazov, J.U. (SCIENCE and SOCIETY, 2024)
The article examines aboit using skill of social-political vocabulary in the works of the Karakalpak poet I.Yusupov. The Arabism is proven in the basis of the examples taken from the works of art. The semantics of acquisition words is analyzed in the Karakalpak language.
Keywords: lexicology; vocabulary; terms; Arabism; literary language; historical vocabulary; Turkish languages; etymological dictionary